Analisis Kadar Fenolik dan Flavonoid Total pada Teh Hijau (Camellia sinensis) yang Dikeringkan dengan Oven, Solar Dryer dan Pengeringan Tradisional - Rumahombar, Vonny Geminta; Setyowati, Emerita; Rawar, Ellsya Angeline (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2025)
Green tea (Camellia sinensis) is renowned worldwide, not only for its flavor but also for its exceptional health benefits, primarily due to its antioxidant-rich bio active components, including polyphenols like flavonoids and phenolics. The drying process is crucial for preserving these benefits, making the choice of drying method vital. This research examines how different methods—traditional, oven, and solar tunnel drying—affect the total flavonoid and phenolic content in green tea. The findings show that the solar tunnel dryer results in the highest water loss at 90.00%, followed by the oven at 76.92% and traditional drying at 70.00%. The oven also produced the highest total flavonoid levels at 5.1 ± 0.1 mg EK/g, compared to 4.9 ± 0.2 mg EK/g for solar drying and 3.78 ± 0.05 mg EK/g for traditional methods. For total phenolics, oven drying yielded 93 ± 2 mg GAE/g, while solar drying produced 79 ± 3 mg GAE/g and traditional methods resulted in 57 ± 1 mg GAE/g. Selecting the right drying method can significantly enhance the health benefits of green tea, making it an excellent choice for health-conscious consumers.were obtained in the oven drying method of 93±2 mg GAE/g, in the solar tunnel dryer 79±3 mg GAE/g and traditional 57±1 mg GAE/g.space